2017
DOI: 10.4172/2165-7548.1000360
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management Strategies and Time Spent on Scene for Pre-Hospital Analgesia Provision in an Alpine Environment: A Retrospective Study

Abstract: Objective: The delivery of a safe an effective analgesia is a core principle and a priority of prehospital care. Analgesia in hostile environments (mountain settings, etc.) presents various challenges, and the benefit-risk ratio of the procedure should be evaluated. The objective of this study was to examine pain management strategies and the time spent on scene for analgesia provisions in an alpine environment. Methods:We undertook a retrospective study from a single physician-staffed helicopter emergency med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…10,26,27 We found that, as in other prehospital studies, midazolam was frequently coadministered with ketamine. [28][29][30][31] The use of empathy (reassurance, addressing the patient by name, informing the patient about the dissociative effects and the ongoing procedure to reduce emergence reactions and pain) was another frequently proposed intervention. Many participants reported using therapeutic communications such as guiding patients to picture pleasant dreams, with the goal of reducing the occurrence of neuropsychiatric side effects.…”
Section: Methods Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…10,26,27 We found that, as in other prehospital studies, midazolam was frequently coadministered with ketamine. [28][29][30][31] The use of empathy (reassurance, addressing the patient by name, informing the patient about the dissociative effects and the ongoing procedure to reduce emergence reactions and pain) was another frequently proposed intervention. Many participants reported using therapeutic communications such as guiding patients to picture pleasant dreams, with the goal of reducing the occurrence of neuropsychiatric side effects.…”
Section: Methods Of Usementioning
confidence: 99%
“…A retrospective study conducted 6 y prior in the same HEMS reported no use of IM or IN ketamine. 28 Although IM use in pediatrics has been well demonstrated with a good efficacy and safety profile, 26,39 IV use is still preferred in adults because it allows rapid administration of midazolam in the case of unpleasant neuropsychiatric effects. IM administration is associated with more vomiting and a longer recovery time.…”
Section: Methods Of Usementioning
confidence: 99%